A Non‐Randomized Trial of In‐Person Versus Text/Telephone Screening, Brief Intervention and Referral to Treatment for Pregnant and Postpartum Women. Issue 4 (18th November 2021) - Guille, Constance; Maldonado, Lizmarie; Simpson, Annie N.; Newman, Roger; King, Courtney; Cortese, Bernadette; Quigley, Erin; Dietrich, Nicole; Kerr, Anna; Aujla, Rubin; King, Kathryn; Ford, Dee; et al.
Abstract : Background: Systems of care that improve mental health and substance use disorder Screening, Brief Intervention and Referral to Treatment (SBIRT) for pregnant and postpartum women are needed. Aims: The aim of this study is to determine if women receiving prenatal care from January 2020 to April 2021 are more likely to be screened, screen positive, be referred for treatment and attend treatment with technology facilitated SBIRT, compared to women receiving prenatal care and in‐person SBIRT January 2017 to December 2019. Materials & Methods: Technology facilitated SBIRT, designated Listening to Women (LTW), includes text message‐based screening, phone‐based brief intervention, and referral to treatment by a remote care coordinator. A total of 3535 pregnant and postpartum women were included in the quasi‐experimental study and data were collected via text message and Electronic Health Record. Results: In‐person SBIRT was completed by 65.2% (1947/2988) of women while 98.9% (547/553) of women approached agreed to take part in LTW and 71.9% (393/547) completed SBIRT via LTW. After controlling for potentially confounding variables, women enrolled in LTW were significantly more likely to be screened (relative risk [RR]: 1.10, 95% CI 1.03–1.16), screen positive (RR 1.91, 95% CI 1.72–2.10), referred to treatment (RR 1.55, 95% CI 1.43–1.69) and receive treatment (RR 4.95, 95% CI 3.93–6.23), compared to women receiving in‐person SBIRT. Black women enrolled in LTW were significantly more likely to screen positive (RR 1.65, 95% CI 1.35–2.01), be referred to treatment (RR 1.54, 95% CI 1.35–1.76) and attend treatment (RR 5.49, 95% CI 3.69–8.17), compared to Black women receiving in‐person SBIRT. Discussion: LTW appears to increase the proportion of pregnant and postpartum women receiving key elements of SBIRT. Highlights: Technology‐based solutions have the potential to overcome many of the key patient, provider and system‐level barriers that inhibit widespread adoption of evidence‐based screening and referral recommendations for Perinatal Mood and Anxiety Disorders (PMADs), Perinatal Substance Use Disorders (PSUDs), and Intimate Partner Violence (IPV). Listening to Women (LTW), a text message‐based screening, phone‐based brief intervention, and referral to treatment by a remote care coordinator, appears to increase the proportion of pregnant and postpartum women being screened, screening positive, referred to treatment and attending treatment, compared to in‐person Screening, Brief Intervention and Referral to Treatment (SBIRT) during prenatal care. Racial disparities in attendance to treatment identified with in‐person SBIRT were not present with LTW; Black women were more likely to attend treatment with LTW compared to in‐person SBIRT and Black and White women were equally as likely to attend treatment with LTW.